World prices and domestic food price spikes - Zoltán Bakucs; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
In this paper we aim to assess the mechanics of the global food price increases experienced in the recent years, most profoundly during the 2007-2008 food price spikes. At this stage, we aim to test, whether there is an empirically assessable relationship between World agricultural commodity prices, World oil prices and Hungarian producer and consumer food prices. After briefly discussing the background of the food price surge, and some studies empirically assessing it, we estimate a Vector Error Correction Model (VECM) with two long-run relationships, modelling vertical and horizontal price relationships (price transmissions). Preliminary results express (as somewhat expected for a small open economy as Hungary) that global developments have direct and significant effects upon price levels in Hungary regardless whether a vertical or horizontal price dimension is used. Further research will focus on determination of the magnitude, speed of occurrence and duration (needed to return to equilibrium) of the abovementioned global shifters express upon domestic agricultural and food price levels.
Keywords: Q1; 330; agricultural prices; crude oil prices; cointegration; vector error correction; Preiskonvergenz; Agrarpreis; Ölpreis; Lebensmittelpreis; Verbraucherpreisindex; Erzeugerpreisindex; Kointegration; Ungarn